Acolhimento institucional e negligência familiar: a contradição da garantia de direitos - Farias, Kátia da Silva (Universidade Federal do Tocantins, 2022)
The present research entitled “INSTITUTIONAL RECEPTION AND FAMILY NEGLIGENCE: the contradiction of the guarantee of rights”, aimed to address the issue of institutional reception of children under the allegation of family neglect. It is noteworthy that the present research proposed to analyze how the access to social protection policies is materialized for families who had their children welcomed under the allegation of family neglect. Its general objective was to identify how social protection policies enable or not the necessary social protection for families who had their children referred to the institutional shelter service under the allegation of family neglect. This is a bibliographical and documental research, in which Marx's dialectical-historical materialism was used as a method for analyzing the results. Data collection followed all the steps foreseen in the research project schedule approved by the Research Ethics Committee of the Fundação Universidade Federal do Tocantins (UFT). Then, the documents contained in the procedural records extracted from the Electronic Judicial Process system - E-PROC of the Court of Justice of the State of Tocantins (TJTO) were analyzed, with emphasis on the Individual and Family Assistance Plan (PIA), in the reports included by the technical teams and other actors participating in the process. As a sample, an analysis of 17 (seventeen) cases of children in institutional care was carried out under the allegation of family neglect, in the period between January and December 2019. We emphasize that, among the elements found during the research, we highlight the great emptying of the procedural flow with regard to the systematic presentation of network performance before and after the application of the measure. The absence of these elements compromises a more forceful analysis in relation to the reception decision on the grounds of family neglect, which, in turn, corroborates the understanding of the link between neglect as a synonym for poverty. We also point out that the construction of the PIA that does not follow the established regulations and presents itself only as a bureaucratically constructed tool. It is important to point out that it was not possible to complete the objectives in their entirety. However, the elements found were sufficient for a deep analysis of institutional care and the existing contradiction between the effectiveness of social protection for families who had their children welcomed under the allegation of family neglect.